The Impact of COVID-19 Pandemic on the Mental Health of 3rd-Year Medical Technology Students in a University in Manila, Philippines A.Y. 2022-2023 - Malang, Emmanuel DS; De Guzman, Angela Marie A.; Dizon, Sally Nicoile S.; Garcia, Katrene Marie M.; Garcia, Krishia Marie M.; Gogolin, Penelope Portia P (Future Science / FSH-PH Publications, 2023)
Having good mental health is crucial throughout one's entire life, starting from early stages like childhood and adolescence, and continuing through adulthood and beyond. This research is a quantitative research approach and a correlational research design that aims to conduct a survey to assess the impact of the COVID-19 pandemic on the Mental Health of 3rd-Year Medical Technology College Students in a University in Manila. The researchers conducted an online survey consisting of 3rd-year medical technology students which has 317 as the overall population and 174 as respondents and were computed using an online statistical program, Raosoft. The online survey is only accessible to 3rd-year college students under the Department of Medical Technology at a University in Manila, Philippines. The tallied data is stored via google sheets. This data is analyzed using the SPSS statistical tool. The results of the computations on the gathered data showed a significant relationship between the respondents’ understanding of COVID-19 and their psychological/mental health status. Consequently, this research study is helpful and beneficial to the students by helping them in gathering more knowledge about COVID-19 and helping them to control mental health problems in a more efficient way. The results show that the COVID-19 pandemic has both positive and negative impacts on the mental health of students in general. For instance, in positive impact, the majority of students feel at least moderately confident in their ability to manage personal challenges. In negative impact, students sometimes feel that they are unable to control important things in their life.